An investigation of the antimicrobial effect of porphyrin dyed titanium dioxide nanofibers in pure rutile and mixed anatase /rutile phases - Hlabangwane, Kamogelo Sharlyn (Rhodes University, 2026)
South Africa and many other nations face an issue of a decline in the quality of fresh water. One of the factors causing this decline is contamination by biological components such as bacteria and other microorganisms present in the water. Over time, microorganism can mutate and become resistant to common available treatments. The World Health Organisation has reported that antimicrobial resistance is one of the top 10 health threats that humanity faces today. Alternative therapies such as antimicrobial photodynamic inactivation (aPDI) are methods that can be used to inactivate bacteria while reducing the possibility of antimicrobial resistance. The method uses a combination of light, a photosensitiser and molecular oxygen to generate reactive oxygen species that can be used to target microbial tissue. In this work asymmetric and symmetric tin (II) and indium (III) porphyrins functionalised with methoxy and thiomethyl substituents were adsorbed onto mixed phase anatase/rutile titanium dioxide (TiO2) nanofibers and onto rutile titanium dioxide nanofibers. The effects of metalation, symmetry of the porphyrins and adsportion onto different phases of TiO2 nanofiber are explored and reported on in this work. The porphyrins exhibited good photophysical properties with high singlet oxygen quantum yields and low fluorescence. Staphylococcus aureus, Escherichia coli and Candida albicans were the model microorganisms use in the aPDI studies. The results obtained in this research showed the porphyrins and nanofibers were not effective in the inactivation of E. coli and C. albicans, however, upon adsorption with metalloporphyrins both the mixed-phase anatase/rutile TiO2 nanofiber and rutile TiO2 nanofiber were able to inactivate S. aureus. Reusability studies indicated that the mixed-phase anatase/rutile TiO2 nanofibers have good potential in multiuse applications in the inactivation of S. aureus. Based on the results obtained in this research, it can be concluded that the porphyrins and nanofibers have a synergetic effect that increases efficacy in the eradication of microorganisms for S. aureus.
Keywords: Nanofibers (http://id.loc.gov/authorities/subjects/sh2007004894); Titanium dioxide (http://id.loc.gov/authorities/subjects/sh85135627); Active oxygen (http://id.loc.gov/authorities/subjects/sh85000738); Staphylococcus aureus (http://id.loc.gov/authorities/subjects/sh85127365); Escherichia coli (http://id.loc.gov/authorities/subjects/sh85044799); Candida albicans (http://id.loc.gov/authorities/subjects/sh85019564); Metalloporphyrins (https://www.wikidata.org/wiki/Q5999892); Antimicrobial photodynamic therapy (https://www.wikidata.org/wiki/Q125803124)